Pollution Index Assessment of Lake Maninjau Water Quality Status - Jefri Kurniawan; Indang Dewata; Nurhasan Syah; Syafrijon; Dhesya Ardiarini (Jurnal Penelitian Pendidikan IPA, 2026)
Lake Maninjau with its strategic functions, faces pressures from both climate change and anthropogenic activities that can degrade water quality and ecological functions. This study aims to determine the water quality status of Lake Maninjau over the 2022–2025 period as an initial step to support lake restoration and the achievement of Sustainable Development Goal (SDG) 6. Surface water samples were collected twice a year from six stations representing the lake's spatial characteristics using the grab sampling method. Analyzed parameters included pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and phosphate (PO4) following methods established in the Indonesian National Standards and relevant international standards. The water quality status was assessed using the Pollution Index method based on the Decree of the Minister of State for the Environment Number 115 of 2003. The results revealed fluctuating temporal shifts throughout the observation period. In 2022, water quality ranged from good conditions to light pollution. Conditions deteriorated during 2023–2024, with the majority of stations classified as light pollution. By 2025, all monitoring sites recovered to the good conditions. The observed fluctuating patterns of the Pollution Index during the 2022–2025 period indicate that the Lake Maninjau aquatic system remains highly vulnerable to dynamic external pressures, such as organic load accumulation and the lake's natural hydrological dynamics in the form of upwelling events. Consequently, consistent nutrient load reduction is urgently required, particularly through the regulation of floating net cage capacities based on carrying capacity assessments and structured water quality monitoring.